(untitled) (Research, Society and Development, 2021)
Report the experience of carrying out an extension project in the pandemic by COVID-19 using technologies to carry out health education. This is an experience report of descriptive nature, using the method of systematization of experiences proposed by Oscar Jara Holliday. The use of technologies such as Instagram proved to be efficient to continue extension activities, enabling information to be provided to a large number of people contributing to the empowerment of the sexual health of pregnant women, and at the same time it was allowed to encourage measures to prevent contagion against SARS-CoV-2. The development of the extension project "Demystifying sexuality during pregnancy" contributed to expand academic training, as well as cooperated to build a society aware of the importance of sexual health by making them empowered about sexual function in pregnancy.